2015
DOI: 10.1111/jocs.12593
|View full text |Cite
|
Sign up to set email alerts
|

Right Anterolateral Thoracotomy in the Repair of Atrial Septal Defect: Effect on Breast Development

Abstract: Although it is safe, the RALT is associated with the potential to effect unilateral breast development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…The authors recommended abandoning right anterolateral thoracotomy in prepubescent female patients, although subjective satisfaction with the cosmetic results was high [ 15 ]. Isik and his colleagues also concluded that ALMT was associated with the potential to affect unilateral breast development [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommended abandoning right anterolateral thoracotomy in prepubescent female patients, although subjective satisfaction with the cosmetic results was high [ 15 ]. Isik and his colleagues also concluded that ALMT was associated with the potential to affect unilateral breast development [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a balancing argument, they reported that 76% of patients in the thoracotomy group perceived their cosmetic results as excellent in contrast to 39% of patients in standard full median sternotomy group. Similarly, Isik and colleagues 33 reported breast asymmetry occurrence in 60% and mild sensory deficit in the mammary area in 16% of women who underwent ASD closure in prepubertal age via anterolateral thoracotomy. Clearly, the anterolateral thoracotomy approach should be used cautiously, if at all, in prepubertal female patients.…”
Section: Right Thoracotomymentioning
confidence: 85%
“…10 While similar access can be achieved via a right anterolateral thoracotomy, 16,21,22 some cosmetically undesirable outcomes have been reported. 30,33 Impaired breast development is of concern, as it is challenging to determine the appropriate length and position of the incision in a child with respect to the immature breast tissue. According to Bleiziffer and colleagues 30 right breast asymmetry was reported in 61% of female patients who underwent ASD closure via right anterolateral thoracotomy before onset of puberty compared with no such events in standard full median sternotomy group.…”
Section: Right Thoracotomymentioning
confidence: 99%
“…4 Right mini-thoracotomy surgical approach provides an optimal exposure of both RA and LA, facilitating the search for abnormal venous drainage, especially if the skin is incised a few centimeters more anterior than is usually done for a right mini-thoracotomy through the fourth intercostal space across the anterior axillary line. 5 In this particular case, it was very easy to identify all anatomical structures, and the correction was accomplished without complications. The femoro-femoral cardiopulmonary bypass was optimal because it left the IVC free from a venous cannula, which could interfere with the patch suture.…”
Section: Commentmentioning
confidence: 88%